Villes moyennes et dévitalisation des centres : les politiques publiques face aux enjeux d’égalité territoriale - Sandrine Berroir; Sylvie Fol; Christophe Quéva; Frédéric Santamaria (Belgeo)
In a context where inequalities are rising between metropolitan areas that agglomerate jobs, firms and populations, and areas that are clearly benefiting less from these assets, this paper analyses the issues of territorial inequalities raised by the current situation of medium-sized cities in France, and the way in which public policies, at national and local scales, are dealing with these issues. More precisely, it analyses the current situation of three medium-sized cities, Forbach, Nevers, Vichy, in which devitalization of city-center is triggered by a shrinking process. This situation raises more acutely the issue of territorial equality at the national and local levels.